ANALISIS FUNDAMENTAL TERHADAP KINERJA KEUANGAN PT ULTRAJAYA MILK INDUSTRY & TRADING COMPANY, TBK. PERIODE 2020-2024 - Youlanda, Sendy Octapia; Hutabarat, Desi Lestari; Mulyani, Mulyani (Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the financial performance of PT Ultrajaya Milk Industry Tbk during the 2020–2024 period using fundamental analysis. Financial performance is assessed through several key financial ratios, including liquidity, solvency, profitability, and activity ratios, which reflect the company’s ability to meet its short-term and long-term obligations, generate profit, and utilize assets efficiently. The method used in this research is a quantitative descriptive approach, utilizing secondary data sourced from the company's audited financial statements. The analysis results indicate that PT Ultrajaya maintains a healthy liquidity level throughout the observed period, with relatively low leverage and consistent profitability. However, certain fluctuations in inventory turnover and return on equity suggest areas for operational improvement. These findings imply that PT Ultrajaya remains financially stable and attractive for investors, but continued efficiency and strategic management are essential to maintain competitive performance in the food and beverage industry. The results of this research are expected to contribute to investment decision-making and academic insights in financial performance evaluation.